2019
DOI: 10.1259/bjrcr.20180109
|View full text |Cite
|
Sign up to set email alerts
|

Gastric lipomas: a case series and review of a rare tumor

Abstract: The purpose of the study was to investigate and review the multimodality imaging findings of gastric lipomas. Seven patients with gastric lipomas identified by CT imaging at a single institution between 2003 and 2017 were retrospectively evaluated. Patient demographics, clinical presentation, non-invasive imaging, endoscopic, and pathological findings were recorded.The most common location for gastric lipoma was the gastric antrum (3/7). The mean lipoma size was 2.7 cm ± 0.8 cm. Six out of seven lipomas demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Well-differentiated liposarcomas account for 40% of all liposarcomas. Their peak incidence is between the 5th and 7th decades [2 , 7 , 13 , 14] .…”
Section: Discussionmentioning
confidence: 99%
“…Well-differentiated liposarcomas account for 40% of all liposarcomas. Their peak incidence is between the 5th and 7th decades [2 , 7 , 13 , 14] .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of gastric lipoma, it strongly suggests the diagnosis by visualization of a well-circumscribed homogeneous mass with fat density ranging between −80 and −120 Hounsfield units. These values are considered pathognomonic and suggest a diagnosis of gastric lipoma, by falling in the expected value range for adipose tissue [ 4 , 5 ]. EUS is another useful imaging study to confirm the hypothesis of gastric lipoma.…”
Section: Discussionmentioning
confidence: 99%
“…Giant gastric lipomas (≥4 cm) are even more unusual [ 3 ]. The vast majority of gastric lipomas are small and discovered incidentally during endoscopic or radiology evaluations [ 4 , 5 ]. The small asymptomatic lesions can be followed without intervention [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antrum was the most common location in their case series, as was in the present case. They concluded that CT is the diagnostic gold standard, surpassing other imaging studies, endoscopy, and even routine endoscopic biopsy in both sensitivity and specificity [16].…”
Section: Discussionmentioning
confidence: 99%